Percepções sobre a qualificação profissional para adolescentes egressos e em cumprimento de medidas socioeducativas de prestação de serviços comunitários ou liberdade assistida: o projeto Tempo de Despertar - Bastos, Stephanie Freires (2019)
The objective of this dissertation is to analyze the possibilities of professional qualification for the social transformation of the adolescents who are graduates and in fulfillment of socio-educational measures of community service and / or assisted freedom, based on the case study of a group of the Learning Program entitled Awakening Time. The Project is developed through a partnership signed between the Municipality of Araucária, the Public Ministry of the State of Paraná and a teaching institution that we will call a Keeping Institution to maintain secrecy. It is based on the foundations of historical and dialectical materialism, and it is used as methodology the bibliographical research for the structuring of the theoretical reference, documentary research of the legislation referring to adolescents in fulfillment of socio-educational measures, and instruments of data collection as semi-structured interviews carried out with the adolescents and technical team participating in the Program to carry out the analysis of possible perceptions about the transformation of the social reality of the adolescents in question. We sought to present results about the possibilities of transforming the social reality of the adolescents who participated in the program, as well as verifying the level of schooling and its future perspective. The intention was to understand if the strategy of the development of Learning Program, as a possibility of social interaction in new environments, brought to the adolescent a new perspective of life. It is concluded that the passage through the Project Time of Awakening facilitated to make possible a change in the social reality of the adolescents of socioeducation, in order to compete for non-recurrence in situations that led them to the exercise of socio-educational measures.